The curse of Pietro Houdini : a novel - Miller, Derek B., 1970- (Avid Reader Press, 2024)
In 1943, 14-year-old Massimo, rescued by a mysterious man called Pietro Houdini who preserves the treasures within the Benedictine abbey's wall, accompanies him on a World War II art-heist adventure where they lie, cheat, steal, fight, kill and sin to survive, while smuggling Renaissance masterpieces they've rescued from the "safe keeping" of the Germans.